Use of antipsychotic and sedative medications in older patients in the emergency department. Issue 3 (25th November 2021) - Kennedy, Maura; Koehl, Jennifer; Gao, Jingya; Ciampa, Katherine A.; Hayes, Bryan D.; Camargo, Carlos A.
Abstract: Background: Antipsychotics and sedatives are used to treat agitation in the emergency department (ED) but carry significant risk in older adults. Our objective was to determine factors associated with their administration to older ED patients. Methods: This was an observational study using data from the 2014–2017 National Hospital Ambulatory Medical Care Survey. We identified ED visits for patients aged ≥65 years and determined whether an antipsychotic or sedative was administered. Visits related to substance use/withdrawal, other psychiatric complaints, and intubation were excluded. We performed multivariable logistic regression to identify risk factors for antipsychotic or sedative administration. Results: Of the 78.7 million ED visits that met inclusion criteria, 3.5% involved at least one dose of antipsychotic or sedative medication; 13% involved an antipsychotic and 92% a sedative. Factors associated with antipsychotic administration included nursing home residence (adjusted odds ratio [aOR]: 2.67; 95% CI: 1.05–6.80), dementia (aOR: 5.62; 95% CI: 2.44–12.94), and delirium (aOR: 7.33; 95% CI: 2.21–24.32). Sedative administration was positively associated with CT or MR imaging (aOR: 1.86; 95% CI: 1.42–2.43), urbanicity of ED (aOR: 1.46; 95% CI: 1.02–2.08), and female gender (aOR: 1.47; 95% CI: 1.08–1.99) and negatively associated with older age (age: 75–84; aOR: 0.67; 95% CI: 0.49–0.91; age: 85+; aOR: 0.63; 95% CI: 0.45–0.88; reference age: 65–74 years). Antipsychotic and sedative administration were associated with prolonged ED lengths of stay and hospital admission. Conclusion: We identified patient‐ and facility‐level factors associated with sedative and antipsychotic administration in older ED patients. Antipsychotic and sedative administration were associated with prolonged ED lengths of stay and hospital admission. Abstract : See related editorial by Lee . in this issue.